Inexpensive and colorimetric RNA detection at ambient temperature with a cell-free protein synthesis platform - Toparlak, ÖD; Notarangelo, M; Quattrone, A; Pizzato, M; Mansy, SS (BioMed Central, 2024)
While many proposals of paper-based diagnostics utilize cell-free gene expression systems, these assays oftentimes suffer from the need for temperature cycling and high operational costs, particularly for developing countries. Here, we explore and report the experimental conditions for the colorimetric detection of viral RNA with an in vitro transcription/translation assay that uses crude E. coli extracts at room temperature where the signal amplification is aided by body heat. Clinically-relevant concentrations of RNA (ca. 600 copies/test) were detected from synthetic RNA samples. The activation of cell-free gene expression was achieved using toehold-switch-mediated riboregulatory elements that are specific to RNA sequences. The colorimetric output was generated by the α-complementation of β-galactosidase ω-fragment (LacZω) with cell-free expressed LacZα, using an X-gal analogue as a substrate. The estimated cost of a single reaction is as low as ~ 0.26 euro/test, which may help to facilitate the accessibility of the diagnostic kit in developing countries. With future optimizations and bacterial strain engineering, production costs can be even further brought down, and the test times can be shortened. Graphical Abstract: